Radiation from matter entrainment in astrophysical jets: The AGN case - Araudo, Anabella Teresa (2011)
Jets are found in a variety of astrophysical sources. In all the cases the jet propagates with a supersonic velocity through the external medium, which can be inhomogeneous, and inhomogeneities could penetrate into the jet. The interaction of the jet material with an obstacle produces a bow-like shock within the jet in which particles can be accelerated up to relativistic energies and emit high-energy photons. In this work, we explore the active galactic nuclei scenario, focusing on the dynamical and radiative consequences of the interaction at different jet heights. We find that the produced high-energy emission could be detectable by the current γ-ray telescopes. In general, the jet-clump interactions are a possible mechanism to produce (steady or flaring) high-energy emission in many astrophysical sources in which jets are present.